Apresentação PBCIB n. 4, v. 15, 2020 - Rodrigues Hermes de Araújo, Vania; Maria Freire, Isa; Freire, Gustavo Henrique de Araújo (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2020)
Apresentação PBCIB n. 4, v. 15, 2020